In Search of Principles of Good Governance: Lesson Learned from a Series of Workshops on "Islamic Western Dialogues on Governance Values" - Ropi, Ismatu (Studia Islamika, 2004)
In the Indonesia context, issues of good governance have also been an unflagging national agenda. Despite recognition of the importance of good governance, public discourse on this issue has not gained as much attention as it should within this newly democratic country. Following the downfall of the New Order government in 1998,Indonesia has faced the task of rebuilding a social and political system responsive to the changing expectations of the Indonesian people, embodied in the new animating spirit popularly known as Reformasi. This paradigm of reform refers to the wish to see democratic ideals permeate the lives of all Indonesians.DOI: 10.15408/sdi.v11i1.657